The Creative Experiment - Bowra, C. M. (New York Grove Press, 1948)
This book is a kind of sequel to The Heritage of Symbolism published in 1943, and attempts to sketch some main figures and characteristics of the poetry which succeeded that of the post-Symbolists and has played an important part in Europe since 1910. I have, however, adopted a somewhat different method, and discussed, not the complete careers of poets, but what seem to be their most significant works or phases, in the hope that this will make clearer the problems and aims of this movement. As before, I have been inconsistent in my presentation of texts written in foreign languages. I have assumed that few readers will ask for quotations in Modern Greek and Russian, and have given these only in English translations, but that most will know French and be able to manage Spanish with literal versions to help them. I am indebted to the kindness of friends who have helped me, especially to Dr. S. Rachmilevitsch, Mr. I. Berlin, Mr. A. E. Sloman, Miss Helen Gardner, and Professor R. M. Dawkins; to Professor J. Mavrogordato for allowing me to use some of his forthcoming translations of Cavafy; to Mr. J. M. Cohen for similar help with Alberti; and to Mr. Herbert Marshall and the Pilot Press Ltd. for permission to quote from his Mayakovsky and his Poetry.C. M. BOWRAOXFORD February 1948
Keywords: Esthetics